First report of the fruit-piercing moth, Gonodonta nutrix Stoll, 1780 (Lepidoptera: Erebidae) in Colombia, with notes on its morphology and biology - Yenifer Campos-Patiño; Rubilma Tarazona-Velásquez; Carlos E. Sarmiento; Erika Valentina Vergara-Navarro (Revista Chilena de Entomología)
In February 2023, an outbreak of lepidopteran larvae was observed on a soursop grove (Annona muricata L.; Magnoliales: Annonaceae) at the Agrosavia Palmira Research Station in Valle del Cauca, Colombia. The adult moth was identified as Gonodonta nutrix Stoll (Lepidoptera: Erebidae), a species found from North to South America. The larvae of G. nutrix typically target plants in the Solanaceae family, especially Brunfelsia americana L. and Solanum lycopersicum L. (tomato), as well as species within the genus Annona L. (Annonaceae). The moths can damage the skin of these fruits and occasionally harm citrus fruits with their mouthparts. This study presents information on the morphology and biology of G. nutrix, including life-cycle data and a life table. The larvae were found to be parasitized by a braconid parasitoid from the genus Glyptapanteles Ashmead, 1904 (Hymenoptera: Braconidae: Microgastrinae). Future research is needed to quantify the level of parasitization by Glyptapanteles sp. on G. nutrix and to assess its potential as a biological control agent. Additionally, we provide information on the geographical distribution of G. nutrix in Colombia and the New World, drawing on scientific literature, GBIF data, and citizen science contributions. An examination of entomological collections from six Colombian museums revealed a specimen dating back to 1978, however, this is the first written record of G. nutrix in Colombia.